2023
DOI: 10.35848/1347-4065/acb361
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic focusing using a stacked thin-plate region

Abstract: This paper describes a stacked thin-plate region for focusing the transmitted waves. The region was designed to focus the wave field in the bulk medium by utilizing the dispersion nature of Lamb waves. The first numerical calculation proved that an incident plane wave changes the wavefront in a stacked thin-plate region because of the different phase velocities in plates with different thicknesses, and the resulting transmitted wave was focused at the target. Second, when a delayed longitudinal wave was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Fukuchi et al showed that ultrasonic wave propagation can be controlled by attaching a thin plate buffer to the phased array transducer. 27) Here, the imaging of the reflection source is discussed.…”
Section: Overview Of the Phased Array Imaging Using A Stacked Plate B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuchi et al showed that ultrasonic wave propagation can be controlled by attaching a thin plate buffer to the phased array transducer. 27) Here, the imaging of the reflection source is discussed.…”
Section: Overview Of the Phased Array Imaging Using A Stacked Plate B...mentioning
confidence: 99%
“…25,26) Meanwhile, Fukuchi et al showed by numerical analysis that ultrasonic focusing in a material beyond the diffraction limit is possible using a buffer consisting of stacked thin plates. 27) Our recent study presented that the multiple reflections at the buffer ends affects the PA imaging. 28) In the present study, the characteristics of defect imaging in the material are numerically analyzed considering the features of the thin plate buffer.…”
Section: Introductionmentioning
confidence: 98%